If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6 + -1d) = 18 (6 * 3 + -1d * 3) = 18 (18 + -3d) = 18 Add '-18' to each side of the equation. 18 + -18 + -3d = 18 + -18 Combine like terms: 18 + -18 = 0 0 + -3d = 18 + -18 -3d = 18 + -18 Combine like terms: 18 + -18 = 0 -3d = 0 Solving -3d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Divide each side by '-3'. d = 0 Simplifying d = 0
| 1.2x+3.7=2.2-4.5 | | 6h-7=-73 | | -1r=6 | | x^2y^2=2x | | ln(x)+5=0 | | (5)(-10)= | | x-8y=-11 | | 3x+4x+5x=90 | | 333x-54=7 | | 55x+5y=25 | | (13)(0)(-16)= | | 2(7-7x)=2x+4 | | 4p^2+7p-2=0 | | 2(7-7x)=2x-4 | | 114-2x=34x+18 | | p+6/3=4p+3/8 | | (-7)(4)(3)= | | 1/3(p-3)=114 | | (-5)(2)(-3)= | | 2(x-1)-4=-2 | | 6x^2+x^2-24x-4=0 | | 2x-1-4=-2 | | 2p+4q=12 | | 3x^2+12x=1 | | 2g^2-35g+17= | | 4x^2-16x+7= | | m^2-7m-18= | | 8m^3+14m^2-20= | | 5x+8y=55 | | -27+13= | | x-(-2)=-20 | | 21=4-r |